Investigation of Sorption Activity of Brown Peat Moss Powder; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Blokhina E.; Kelus N.; Krivoshchekov S. V. Sergey Vladimirovich; Kokova D.; Chuchalin V. (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen